ANALISIS JUMLAH KEPALA KELUARGA DAN HARGA TERHADAP PERMINTAAN RUMAH SUBSIDI PADA PT. KALTIM MANDIRI DEVLOPMENT DI KELURAHAN TELUK BAYUR: ANALISIS JUMLAH KEPALA KELUARGA DAN HARGA TERHADAP PERMINTAAN RUMAH SUBSIDI PADA PT. KALTIM MANDIRI DEVLOPMENT DI KELURAHAN TELUK BAYUR - Lisa Puspitasari (Prodi Ekonomi Pembangunan, Universitas Muhammadiyah Berau, 2021)
In order to support the provision of homes for the MBR group, the government provides a series of programs so that the house can be affordable by the community. The problem of housing and settlements in bayur Bay Village is actually inseparable from the dynamics that develop in people's lives and existing government policies. This condition is interesting to research in order to provide optimal benefits, both to consumers and developers. The purpose of this study is 1) Finding the factor of the number of family heads and prices that affect the demand for subsidized houses in PT. Kaltim mandiri development in Bayur Bay Village, 2) Found the magnitude of the influence of each factor on the demand for subsidized houses in PT. Kaltim mandiri development in Bayur Bay Village. The study used secondary data. The data analysis method uses multiple linear regression analysis. Based on the results of the analysis found that of the five variables used in this study only one variable had a positive or significant effect and the value of t calculated greater than t table i.e. variable number of family heads and price variables did not have a positive or significant effect on the demand for subsidized houses. From the results of multiple regression analysis obtained variables that have the greatest influence on the demand for subsidized houses, namely the varying number of family heads, both price variables. From the results of the analysis of the coefficient of determination R Sqaure known 67.7% of the demand for subsidized houses can be explained by variables in the number of family heads and prices. While 46.3% of the demand for subsidized homes was affected by other variables not studied in the study.